Analisis Implikasi Pengesahan RUU TNI Dalam Sinergi Sipil-Militer dan Konsolidasi Demokrasi di Indonesia - Nur Fathoni, Yuzak; Daffa Ahmad, Akhdan; Rau’atur Rushufah, Rana; Sipayung, Jose Benrivo; Indrawan, Jerry (Global Komunika : Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to provide an analysis of the impact of the ratification of the TNI Bill on the dynamics of relations between the military and civilians which produces 2 research questions, namely With the ratification of this TNI Bill, how can it change the Synergy between Civil and Military Institutions? And What is the impact of the ratification of the TNI Bill on the sovereignty of Democracy in Indonesia. The above objectives are attempted to be achieved by correlating the theory of Civil-military relations, democratic consolidation, and the concept of civil supremacy which are packaged in the form of descriptive qualitative research. research used to explore and interpret the meaning of a social phenomenon. The results obtained from this study are that the TNI Bill could be a threat to the implementation of democracy in Indonesia, with the revised article of the article which is considered to have changed the democratic order and threatens the division of the military and civilians. Of course, this can be a real threat and it is possible that in the future the power held by the military could increase and will also recreate the concept of ABRI's dual function in regulating bureaucracy in Indonesia. So from this research it can be concluded that the TNI Bill will be one of the policies that has the potential to bring big problems because it has damaged the democratic order, especially regarding public participation in regulating the bureaucracy.